Performance of timber buildings under high wind loads - Rosowsky, David V (Progress in structural engineering and materials, 2002)
Timber structures often represent the largest percentage of structures built in regions at greatest risk of hurricanes and other high wind events. In countries in which wood structures are common, they often comprise the majority of residential, light commercial, and other low‐rise structures. This paper addresses some of the important issues in the performance of wood buildings subject to high wind loads. Implications for design are addressed and recent and on‐going research is discussed. Developments in the codes and standards areas and future research directions also are discussed.